Quantification of improvement in triathlon swimming performance by textile speedsuits - Ueberschär, O.; Schleichardt, A.; Buchhop, L.; Fichtner, I.; Moeller, T. (Sports Engineering, 2018)
To quantify swimwear-induced differences under triathlon-specific conditions, we compare the swimming performance, the metabolic cost, and the standardised passive drag of well-trained triathletes when wearing (1) five speedsuit models by different manufacturers from 2017, (2) usual swimming trunks/swimsuits (men/women), and (3) individually preferred competition trisuits. Because of the complexity of the underlying hydrodynamic and biomechanical effects, three separate experimental stages were realized, each with 6-12 well-trained short- and middle-distance triathletes (male and female, mean age 22 ± 5 years) from the German national elite or junior elite level. All measurements were conducted on the basis of real athletes` motion in the water to correctly account for all relevant effects, including skin and muscle vibrations. First, the athletes took part in a series of 100 m short-distance tests at maximal effort in a long-course pool to quantify swim-time differences in absolute terms. Second, the subjects completed multiple submaximal 400 m tests at 95% of their individual maximal speed in a swimming flume, with their swimwear-related differences in metabolic load being explored in terms of blood lactate and heart rate. Third, the passive drag of the triathletes was measured in the flume during a towing test under standardised conditions in velocity steps of 0.2 m/s within the triathlon-relevant range of 1.1-1.7 m/s. In all three test stages, the speedsuits exhibited performance advantages over trunks/swimsuits: in the 100 m maximal test, the mean swim time with speedsuits decreased by 0.99 ± 0.30 s (= - 1.5%). During the 400 m submaximal flume test, the mean heart rate showed a reduction of 7 ± 2 bpm (= - 4.0%), while the post-exercise blood lactate accumulation decreased by 1.0 ± 0.2 mmol/L (= - 26.2%). Similarly, the passive drag in the towing test was lowered by 3.2 ± 1.0 W (= - 6.9% as for normalised power and - 5.2% as for normalised force) for the speedsuits. Wearing speedsuits instead of usual trunks/swimsuits is shown to improve the swimming performance and to reduce the metabolic cost for well-trained triathletes under triathlon-specific test conditions. The reduction in passive drag of the passively towed athlete`s body due specific speedsuit surface textures seems to be only one reason for performance advantages: the effective reduction in muscular, soft tissue, and skin vibrations at the trunk and thighs during active propulsive motion of the swimmer seems to further contribute substantially.